FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN PASAMAN BARAT - Novtarisa, Dania; Ansofino, Ansofino; Malinda, Yola (Pendidikan Ekonomi, 2014)
ABSTRACTÂ Issues that are examined in this study are the factors that affect the property tax receipts in West Pasaman period of 2001 to 2011. The purpose of this study was to analyze the factors that affect the property tax receipts in Pasaman West. The methodology used in this study is the method of OLS ( Ordinary Least Square). The data used are time series data such as GDP per capita annual data. the number of mandatory property tax, and investment in West Pasaman , collected through documentation related to service agencies.First results showed that :The factors that influence the acceptance of property tax in West Pasaman : 1 ) GDP per capita has a positive effect with a coefficient value of 0.021 . 2 ) The number of taxpayers earth and building a positive effect with coefficient value of 16 389 . 3 ) Investment positive effect with coefficient of 0.004 . Second : GDP per capita is not significant to the property tax receipts in West Pasaman where tcount < table = 1.8375 < 2.365 . GDP per capita is not significant because the value of GDP received by the public does not increase the asset population in West Pasaman and ownership of GDP is only consumed by the public . Third : The number of mandatory property tax has a significant effect on property tax receipts where t count > t table = 2.4753 > 2.365 . Changes in the amount of property tax shall contribute significantly to the property tax receipts are required to increase or decrease the amount of property tax will have an impact on the increase or decrease in property tax receipts Pasaman West . Fourth : Investing is not significant to the property tax receipts in West Pasaman tcount < table = 0.0966 < 2.365 . Investing is not significant because the data collected did not succeed in proving the link between investment and the acceptance of the UN . Because of all this investment is also used to build schools and education are to pay scholarships . So investment is not directly related to property tax receipts . Fifth : GDP per capita , the number of mandatory property tax and investment jointly affect the acceptance of the United Nations indicated by the F - statistic of 12.191 , while the F - table at level Î± = 5 % error obtained R2 values of 4.459 to 0.8393 amounted to 83.93 % , which means the UN acceptance is influenced by variables GDP per capita , the number of mandatory property tax and investment while the rest is explained by other variables .